HUBUNGAN ANTARA MOTIVASI BERPRESTASI DENGAN KOMPETENSI KARYAWAN MANAJERIAL DI PERUSAHAAN TAMBANG - Hurriyati, Dwi (Jurnal Ilmiah Psyche, 2016)
This study aims to determine whether there is a relationship between achievement motivation and competence of employees managerial. The hypothesis of this study is that there is a relationship between achievement motivation and competence of employees managerial.Population and samples in this study were 738 employees, which is obtained through proportionate stratified random sampling technique. Measuring instruments used in this study is the scale of achievement motivation and competence scale. Analysis techniques using simple regression analysis techniques using SPSS version 18.0.Based on the analysis of research data, it is known (r) of 0741 with a coefficient of determination (R Square) of 0.549 and p = 0, 0000 p <(0.01). This means that there is a significant relationship between achievement motivation and competence of managerial employees